2022
DOI: 10.1002/ppul.26019
|View full text |Cite
|
Sign up to set email alerts
|

Impaired exercise outcomes with significant bronchodilator responsiveness in children with prematurity‐associated obstructive lung disease

Abstract: Introduction: Preterm-born children have their normal in-utero lung development interrupted, thus are at risk of short-and long-term lung disease. Spirometry and exercise capacity impairments have been regularly reported in preterm-born children especially those who developed chronic lung disease of prematurity (CLD) in infancy.However, specific phenotypes may be differentially associated with exercise capacity. We investigated exercise capacity associated with prematurityassociated obstructive (POLD) or prema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We have shown that there are three different phenotypes that may respond to bronchodilators, some of which are associated with increased FE NO and atopy. We have also recently showed that preterm-born children with POLD have decreased exercise capacity as well as increased functional residual capacity (FRC) and residual volume (RV) when compared with term-born controls 32. In contrast, those with pPRISm had intermediate decreases in exercise capacity measures but had decreased FRC and RV.…”
Section: Discussionmentioning
confidence: 98%
“…We have shown that there are three different phenotypes that may respond to bronchodilators, some of which are associated with increased FE NO and atopy. We have also recently showed that preterm-born children with POLD have decreased exercise capacity as well as increased functional residual capacity (FRC) and residual volume (RV) when compared with term-born controls 32. In contrast, those with pPRISm had intermediate decreases in exercise capacity measures but had decreased FRC and RV.…”
Section: Discussionmentioning
confidence: 98%
“…Also of interest were the oscillometry measures following exercise. A greater number of children from the POLD group did not achieve maximal exercise testing, and those children with POLD had lower exercise capacity, 20 which may be a mixture of impaired lung function, respiratory symptoms and deconditioning. 38 While exercise is known to potentially cause bronchoconstriction confirmed T A B L E 4 Oscillometry change scores from postexercise to postexercise bronchodilator for preterm obstructive lung disease (POLD), preterm preserved ratio impaired spirometry (pPRISm), preterm (PTc), and term (Tc) controls.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 We have recently described the prematurity-associated PRISm (pPRISm) phenotype 19 and also showed that this phenotype is associated with impaired exercise capacity with reduced O 2 uptake at peak exercise using a cycle ergometer, with little postexercise bronchodilator response. 20 Along with low functional residual and total lung capacities, this perhaps suggests a fixed structural lung disease in a pediatric preterm PRISm population that may have significant long-term impact given the outcomes identified from adult studies. 20 Oscillometry is likely to provide significant information about how the airways and lung tissues may be affected after preterm birth, especially during exercise when dynamic changes of the respiratory mechanics are occurring.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations